2019
DOI: 10.1108/ijm-01-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organisational commitment on employees’ work-related use of online social networks

Abstract: Purpose Although online social networks (SNs) (e.g. Facebook, LinkedIn and Instagram) have been used by employees for various work- or non-work-related motives, there has been lack of research on the use of such networks in the workplace. The purpose of this paper is to draw on commitment theory and the tricomponent attitude model to explain the role organisational commitment plays in predicting the work-related use of online SNs and the mediating role a constructive employee voice may have in this relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…There can be considered many constructive outcomes for ESM in the workplace (Table 1). For example, employees' use of ESM is associated with their work performance (Cai et al, 2018), organizational commitment (Lou et al, 2018, voice behavior and engagement in organizational procedures (Olfat et al, 2020a;Estell and Davison, 2019), improving knowledge management process in the organization (Qi and Chau, 2018), and work-and nonwork-related socialization (Leidner et al, 2018). However, as a source of social interactions, according to the literature review done in Table 1, the role of employees' social-related use of ESM in shaping their behaviors by learning from each other seems to be neglected by the previous studies, especially when it comes to fashion behaviors.…”
Section: Enterprise Social Mediamentioning
confidence: 99%
“…There can be considered many constructive outcomes for ESM in the workplace (Table 1). For example, employees' use of ESM is associated with their work performance (Cai et al, 2018), organizational commitment (Lou et al, 2018, voice behavior and engagement in organizational procedures (Olfat et al, 2020a;Estell and Davison, 2019), improving knowledge management process in the organization (Qi and Chau, 2018), and work-and nonwork-related socialization (Leidner et al, 2018). However, as a source of social interactions, according to the literature review done in Table 1, the role of employees' social-related use of ESM in shaping their behaviors by learning from each other seems to be neglected by the previous studies, especially when it comes to fashion behaviors.…”
Section: Enterprise Social Mediamentioning
confidence: 99%
“…According to a comprehensive recent study conducted by Zhang et al (2019), previous studies have considered several antecedents for the work-related implementation of social information systems such as the supervisors' support, the coworkers' support, the jobrelated demands (Charoensukmongkol, 2014) and technology-organization-environmental (TOE) framework (Tajudeen et al, 2018). Furthermore, a recent study conducted by Olfat et al (2020) showed that organizational commitment can play a predicting role in the workrelated use of public social networks (SNs) like Facebook and Instagram in the workplace. Olfat et al's (2020) study differs from this study in several aspects.…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 99%
“…Furthermore, a recent study conducted by Olfat et al (2020) showed that organizational commitment can play a predicting role in the workrelated use of public social networks (SNs) like Facebook and Instagram in the workplace. Olfat et al's (2020) study differs from this study in several aspects. The most significant one is that the present study is related to the internal platform (ESNs) that is allocated for a particular purpose in organizations.…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…WhatsApp) and wikis (e.g. Wikipedia) (Hamouda, 2018) that have dramatically transformed people's lifestyles and social relationships (Cao et al , 2016; Olfat et al , 2020a). As a social phenomenon, organizations have also been affected by this type of information technology (Cao et al , 2016).…”
Section: Introductionmentioning
confidence: 99%